Characteristics of Microbial Communities and Their Correlation With Environmental Substrates and Sediment Type in the Gas-Bearing Formation of Hangzhou Bay, China - Yu, Tao; Zhang, Meng; Kang, Da; Zhao, Shuang; Ding, Aqiang; Lin, Qiujian; Xu, Dongdong; Hong, Yi; Wang, Lizhong; Zheng, Ping (Frontiers in Microbiology, 2019)
Shallow gas is a kind of natural gas buried in shallow strata, generally, with methane as the main component, endowing it a potential energy resource while also a potential risk to the safety of ground engineering and environment. Microbial activity is usually regarded as an important driving force to generate shallow gas via metabolizing the environmental substrates. Therefore, the research on the microbial communities will be helpful to reveal the distribution of shallow gas in the gas-bearing formation. In this study, 30 sediment samples below the seabed in Hangzhou Bay (China) from depths of 1.5 m to 55 m were collected to investigate their microbial community, environmental characteristics and sediment type (clay or sand). It turned out that the presence of shallow gas had a good correlation with the distribution of archaea rather than bacteria, with the dominant microbe of Bathyarchaeota, Thaumarchaeota and Euryarchaeota in the formation. Methanosarcinaceae and ANME-1a with the capacity of methane metabolism occupied high proportions. The correlation analysis and redundancy analysis (RDA) suggested that ammonium was a key environmental substrate to indicate the microbial community in the formation. The sediment type was proposed to shape environmental substrates in the formation, thus further affecting the microbial communities. The clay strata were demonstrated to have an important role in the generation and distribution of shallow gas, and more attention should be paid in terms of its resource discovery and engineering safety assessment.